The Future Is Now? Parametric Design and Technology in Design Process - Massimiliano Fuksas (Oz, 2016)
I did not want to be an architect, I wanted to be a painter. I’ve never seen myself as an architect in the strict sense of the word. The thought process beyond my work is more similar to that of a visual artist. For example, I’ve always said that when architecture is successful, it turns into sculpture.